Influence of Perfluorodecalin on Growth of Actinomycetes and Intensification of Streptomycin and Daunorubicin Production by the Genus Streptomyces Kind Bacteria in Submerged Culture - V. M. Bakulin; A. S'. Tumanov; E. A. Martinson; S. G. Litvinec; M. K. Bakulin; V. B. Kalininski (Антибиотики и Химиотерапия)
Addition of perfluorodecalin with gas-transporting function to the liquid medium during submerged cultivation of actinomycetes of the genus Streptomyces resulted in higher intensity and level of the biomass synthesis and increased production of streptomycin and daunorubicin. Addition of perfluorodecalin to the medium provided a 2.0-2.3-fold surpass of the maximum antibiotic production (achieved by the 120th-144th hours of the culture growth) vs. the antibiotic accumulation peaks in the control.